The effects of culture and product type on the use of humor in Greek TV advertising: an application of Speck's humorous message taxonomy - Zotos, Yorgos; Hatzithomas, Leonidas; Boutsouki, Christina (My University, 2009)
The present study attempts to add to the growing literature regarding humorous advertising in high context environments such as Greece and the other Mediterranean countries. It content analyzes 447 Greek TVcommercials in order to identzjj the relationship between humor and the natureofproducts. ln this attempt, Speck’s humorous message taxonomy (1991) and Rossiter 6, Percy’s brand attitude grid provide the theoreticalfiamework for the analysis. The various humor types and processes described by Speck’s taxonomy are linked to consumer involvement and motivation. The study analyzes the use of humor and examines the applicability of the humorous message taxonomy in Greek TV advertising based on cross-cultural analysis between Greece and the USA as recorded in Speck’s original study in 1991 (the only study that employs the same theoretical jramework for the analysis of humorous TV advertising).
Keywords: Humorous advertising; Greece; Mediterranean; Commercials; Message taxonomy; Culture type; Product type